Balance of payments adjustment, 1945-1986 - De Vries, Margaret Garritsen (IMF Washington, DCUS, 1987)
Chronologically traces the development of the policies and activities pursued by the fund since 1945 in order to help its members achieve balance of payments adjustment. Explains how balance of payments was achieved in practice and what policies were most effective. Discusses main difficulties members encountered in reducing or eliminating payments desequilibria. Broad topics covered include adjustment under the par value system; 1945-72 which embraces sub-topics including inter alia, the formation and implementation of initial policies and the experience of industrial and developing members in the 1960's. Also discusses adjustment after 1972 focussing on inflation, adjustment policies and debt strategy.